Integrasi MFA-LCC Untuk Pengembangan SOP Pemanfaatan Limbah Padat Pulping Kopi Arabika di Kopi Wanoja Kamojang Kabupaten Bandung - Muhammad Fadlin Zhafrana; Indra Firmansyah (Journal of Science, Technology, and Innovation, 2026)
Solid waste management inefficiencies in the coffee processing operations at Kopi Wanoja have generated environmental burdens and operational cost inefficiencies. This study specifically aims to map material flows through Material Flow Analysis (MFA), calculate life cycle costs using Life Cycle Costing (LCC), identify hotspots of material and cost inefficiencies, and formulate a Standard Operating Procedure (SOP) for solid waste management. The research employed a quantitative descriptive approach with mass balance modeling conducted using STAN 2.7 software, complemented by financial analysis based on the parameters of Net Present Value (NPV), Benefit–Cost Ratio (BCR), and Payback Period (PBP). MFA results identified the pulping stage as the primary hotspot, generating coffee cherry skin waste of 40.63 kg per batch, equivalent to 53.44% of total input. From a financial perspective, LCC analysis indicated that the investment is feasible, yielding an NPV of Rp109,839,471, a BCR of 1.015, and a payback period in the seventh year. In conclusion, the integration of MFA and LCC proved effective in synchronously detecting hidden costs and material inefficiencies compared to conventional cost accounting approaches. These findings provide a scientific basis for developing an SOP aimed at stabilizing green bean yield at approximately ±41.4% while converting disposal costs into revenue through by-product utilization. It is therefore recommended that the company promptly implement the proposed SOP to maintain both economic and environmental sustainability.